PENERAPAN METODE TWO STAY TWO STRAY DALAM UPAYA MENINGKATKAN KETERAMPILAN MENULIS PADA MATERI LAPORAN PENGAMATAN - Rhiantini, Sari; Sunarya, Dede Tatang; Iswara, Prana Dwija (Jurnal Pena Ilmiah, 2017)
This classroom action research  to for the implementate of cooperative learning methode two stay two stray to improve the learning outcomes of  observasion reportin class V A SDN Tegalkalong. This probleam  ussualy because of a lack innovation teachers in learning, students appeared less excited so atmosphere is less active.  A methode of TS-TS is also a way to share knowladge and experience. Result of writing skill observation report for  V A SDN Tegalkalong from pleminary data 4 students (16,6%) to 9 students  (34,6%) from  first cycle, from second cycle 16 students (66,6 %) and last in third cycle 23 students (95,83%) was complete of target 85%. Then we can conclude a methode  of  two stay two stray  can improve the learning out comes  students in observation report.